Evaluating the source, age, thermal history and palaeoenvironments of deposition of Australian and Western Canadian petroleum systems: compound specific stable isotopes coupled with inorganic trace elements - Maslen, Ercin (Curtin University, 2010)
Petroleum geochemistry is an important scientific discipline used in the exploration and production of hydrocarbons. Petroleum geochemistry involves the applications of organic geochemistry to the study of origin, formation, migration, accumulation and alteration of hydrocarbons.Key concepts and applications of petroleum geochemistry include understanding the petroleum systems, biomarkers and stable isotopes for oil‐oil and oil‐source rock correlations and controls on secondary processes (e.g. biodegradation, water‐washing and migration‐contamination) altering the composition and usually the quality of petroleum.In this research, important concepts and novel techniques of petroleum geochemistry have been utilized for characterizing the source rocks, evaluating the thermal history of the source rocks, understanding the age (where possible), establishing the depositional environment and lithology of the source. More specifically, various innovative organic (biomarker and stable isotopes) and inorganic (trace elements) geochemical approaches were undertaken to establish source, age, thermal history and sedimentary depositional environments of petroleum systems in Western Australia and Western Canada petroleum basins.The aim of the study presented in Chapter 2 was to understand the enigmatic occurrence of crocetane (an irregular C20 isoprenoid), that is usuallyfound in sediments associated with gas hydrate settings and used as a molecularindicator for the anaerobic oxidation of methane (AOM), in Devonian sediments and crude oils containing molecular indicators of photic zone euxinia (PZE).This study comprised a detailed molecular and isotopic study of crocetane and Green Sulfur Bacteria (GSB)‐derived carotenoids in Devonian sediments of the Western Canada Sedimentary Basin (WCSB) covering a range of thermal maturities. In addition, a series of oils generated from Devonian source rocks of the basin were analysed for crocetane. Crocetane was found in ten sediments from the WCSB and in seven Devonian WCSB crude oils. Its abundance was found to increase with thermal maturity, whereas the components generated from C40 derived carotenoids of GSB decreased steadily. The preferred proposed natural product precursor for crocetane is thus GSB‐derived carotenoids. This was corroborated by their similar structural features and the δ13C value of combined crocetane and phytane in these samples. Based on the work presented in Chapter 2, it was concluded that crocetane can provide evidence for PZE conditions in highly mature sediments and crude oils of Devonian age.Application of δD values of individual hydrocarbons (isoprenoids and nalkanes) has a great potential to estimate the thermal maturity of sedimentary organic matter. In Chapter 3, to elucidate the effect of thermal history on the δD values of petroleum hydrocarbons, (i) a comprehensive literature review, focussing on variations in δD values of sediment extracts, crude oils (including bulk organic matter and hydrocarbon fractions as well as individual nalkanes and isoprenoids) and kerogen was carried out and (ii) the application of δD values of hydrocarbons as a maturity parameter with new data from Devonian source‐rocks in the WCSB was tested.Previous work has been used to demonstrate systematic variation in D/H of individual compounds in sediments as a function of thermal maturity and our research in Chapter 3 extended the application of D/H of biomarkers to Devonian samples from the Duvernay Formation of the Western Canada Sedimentary Basin (WCSB) which is much older deposits (i.e. Devonian) than previously studied.Based on the work presented in Chapter 3, the n‐alkanes, pristane and phytane from relatively immature sediments have δD values that retain the isotopic signature of their natural product precursors, i.e. biosynthesised lipid components made up of acetyl and isoprene sub‐units, respectively. With increasing maturity, pristane and phytane become more enriched in deuterium (D), while the n‐alkanes generally remain at a constant isotopic composition until an overmature level is reached, at which point there occurs a significant enrichment of D in n‐alkanes. The enrichment of D in pristane and phytane with increasing maturity correlated strongly with changes in traditional maturity parameters including vitrinite reflectance, Tmax, and molecular parameters, providing evidence that D‐enrichment is associated with thermal maturation.The maturity indicator based on compound‐specific δD values has proved useful in cases where traditional biomarker maturity parameters are ineffective, for example at high maturity levels (i.e. % Ro >1.0) or where their associated reactants and products either equilibrate, or are thermally degraded. In addition, such a maturity measurement is applicable to Devonian sediments, where vitrinite reflectance measurements cannot be made because the higher‐plant precursors of vitrinite have not yet evolved.In Chapter 4, an integrated study including organic (stable carbon isotopes of individual hydrocarbons) and inorganic (trace elements) geochemical data, along with statistical analysis (linear discriminant analysis) was carried out for the first time to assess the source and age characteristics of crude oils from Western Australian and Western Canada petroleum basins.A novel rapid, reliable and accurate method of determination of major and trace element contents of crude oils was developed based on Laser Ablation Inductively Coupled Plasma‐Mass Spectrometry (LA‐ICP‐MS). This method has been applied for the first time to a series of petroleum samples for analysis of Fe, Mg, Al, Zn, Cu, Cr, Ni, Co, V, Tm, Mn, Ge, Dy, Si, Pb, B, Sn, Ti, Hg, As, Mo and Se at trace levels, with little or no sample pre‐treatment. δ13C values of individual hydrocarbons were carried out in a systematic manner to compliment the trace element data.The scatter plot of two discriminant functions from the analysis of trace elements (V, Pb, B, Mg, Sn, Ti, Mo and Hg) in crude oils samples confirms the capability for separating samples into their petroleum basins. 91.3% correct classification of the samples analysed was achieved. Analysis using two discriminant functions of combined trace elements (Al, Cr, Ti, Fe, Cu, Si, Tm, Mn, Ge, and Dy) and δ13C of Naphthalene (N), Biphenyl (Bp) resulted in 100% of samples being correctly classified according to their source rock age.In summary, based on the work presented in Chapter 4, the application of linear discriminant analysis and the stable carbon isotope values and trace element concentrations has allowed the classification of crude oils to their geographical (or basinal) sources and age. The use of complimentary inorganic trace element and organic stable isotope techniques for crude oil samples has been demonstrated as a new highly discriminant tool for petroleum exploration.The research presented in Chapter 5 is aimed at establishing the factors controlling the stable carbon isotopic compositions of individual aromatic hydrocarbons analysed by compound specific isotope analysis (CSIA) in crude oils from Western Australian petroleum basins of varying age and facies type but of similar thermal maturity. An evaluation of the data on δ13C of individual aromatic hydrocarbons, like alkylbenzenes, alkylnaphthalenes, alkylphenanthrenes and methylated biphenyls has been carried out to confirm the source and age of these oils and to understand why the Sofer plot is ineffective in establishing source of Western Australian petroleum systems. Previous isotopic work on the oils was mainly based on their bulk δ13C values of saturate and aromatic hydrocarbons. Western Australian oils seemed to follow an erroneous trend regarding their depositional environments (marine vs terrigenous) when they were assessed using only bulk isotopic values.The interpretation of the data presented in Chapter 5 showed that the oils where the δ13C of 1,6‐DMN (dimethylnaphthalene) and 1,2,5‐TMN (trimethylnaphthalene) isomers is most negative are probably derived from a marine source, whereas oils containing 1,6‐DMN and 1,2,5‐TMN with a less negative value are representative of a terrigenous source. The δ13C values falling in between probably have mixed source(s). Less negative δ13C values of 1‐MP and 1,9‐DMP isomers probably reflects the varying inputs of terrigenous organic matter to the source‐rocks of the oils. In addition, plots of P (phenanthrene) /DBT (dibenzothiophene) and Pr (pristane)/Ph (phytane) versus δ13C of DMP (dimethylphenanthrene), 1,6‐DMN, 1,2,5‐TMN, 1‐MP (methylphenanthrene) and 1,9‐MP are constructed to establish the end‐members of terrigenous and marine sourced oils. The ratio of P/DBT and/or the ratio of Pr/Ph and δ13C of aromatic isomers (such as 1,6DMN, 1,2,5‐TMN, 1‐MP and 1,9‐MP) when coupled together, provide a novel and convenient way of establishing crude oil source rock origin and sometimes even lithologies.In summary, oils from terrigenous depositional environments based on their bulk δ13C values were classified as marine based on their δ13C values of individual aromatic compounds. The compound specific isotope data of the aromatic hydrocarbons obtained for the oils may provide opposite conclusions regarding the source of the oils compared to bulk data using the Sofer plot. Thus, great care must be taken when interpreting isotope values of hydrocarbons, particularly those that are only based on bulk parameters.Ultimately, this project has demonstrated that analyses of molecular fossils (biomarkers) and their stable isotopic compositions (δ13C and δD) complemented with trace element data provides an excellent novel tool for better understanding the basic concepts in petroleum basins and for solving a wide range of problems during petroleum exploration.